Three new species of Oppioidea (Acari: Oribatida) from India - Ermilov, Sergey G.; Kalúz, Stanislav (Zootaxa, 2013)
Three new oribatid mite species of the superfamily Oppioidea—Cycloppia asetosa sp. nov., C. spindleformis sp. nov. and Hammerella (Hammerella) excisa sp. nov.—are described from India. The genus Cycloppia and subgenus Hammerella (Hammerella) are for the first time recorded in India. Cycloppia asetosa sp. nov. differs from all species of Cycloppia by the rostrum with indentation and the absence of interlamellar setae and their alveoli. Cycloppia spindleformis sp. nov. dif-fers from all species of Cycloppia by the presence of interlamellar alveoli only. Hammerella (H.) excisa sp. nov. differs from all species of Hammerella (Hammerella) by the rostrum with indentation and the presence of notogastral setae c. The identification keys to all known species of Cycloppia and Hammerella (Hammerella) are provided.